2012
DOI: 10.1590/s1516-35982012000300038
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of mannan-oligosaccharides offered in milk replacers or calf starters and their effect on performance and rumen development of dairy calves

Abstract: -The objective of this study was to evaluate the route of administration of mannan-oligosaccharides in the diet of dairy calves and their effects on performance and plasma parameters indicative of rumen development.Following birth, twenty-four male Holstein calves were used in a completely randomized design and assigned to the following treatments: Control; 4 g/d Bio-Mos ® (Alltech Biotech.) added to starter concentrate; and 4 g/d Bio-Mos ® mixed into milk replacer. Animals were housed in individual hutches wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
18
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 27 publications
4
18
1
1
Order By: Relevance
“…The present study results were in agreement with the results of Adams et al (2008); Frizzo et al (2010) who reported no significant effect of feeding probiotic on serum urea levels in calves. Silva et al (2012) also reported that MOS feeding did not affect plasma urea nitrogen concentration in calves. AlSaiady et al (2010) reported significantly higher serum urea concentration in calves supplemented with cultured Lactobacillus acidophilus 27sc probiotic.…”
Section: Triglyceridesmentioning
confidence: 92%
See 1 more Smart Citation
“…The present study results were in agreement with the results of Adams et al (2008); Frizzo et al (2010) who reported no significant effect of feeding probiotic on serum urea levels in calves. Silva et al (2012) also reported that MOS feeding did not affect plasma urea nitrogen concentration in calves. AlSaiady et al (2010) reported significantly higher serum urea concentration in calves supplemented with cultured Lactobacillus acidophilus 27sc probiotic.…”
Section: Triglyceridesmentioning
confidence: 92%
“…The results were in accordance with the results of Adams et al (2008) and Frizzo et al (2010) who reported no significant difference in serum glucose levels of probiotic group and control group. Rekiel et al (2007) and Silva et al (2012) reported that prebiotic supplementation had no effect on plasma glucose levels in pigs and calves respectively. The results were in contradiction with the results of Abdel Fattah et al (2009) who reported significant lower values of serum glucose levels in broilers treated with probiotic, prebiotic and synbiotic.…”
Section: Glucosementioning
confidence: 99%
“…Ionophores have been successfully used for this purpose; however, the inclusion of these additives in animal feed is banned in the European Union (SILVA et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The main additives used in Brazil are ionophores, however, problems with toxicity and bacterial resistance, prevent the use of these products as food additives for ruminants in many countries (BARTON, 2000). As a consequence, the scientific community actively seeks alternative food additives without leaving residues in animal products and, at the same time, reducing the release of polluting gases to the environment (SILVA et al, 2012). Among the options, copaiba oil-resin (Copaifera sp.)…”
Section: Introductionmentioning
confidence: 99%